CREATING TWO, THREE, MANY CHE: THE INTERNATIONALIZATION OF REVOLUTIONARY IDEAS THROUGH ERNESTO GUEVARA IN TRICONTINENTAL JOURNAL (1967-1990) - Calvo González, Patricia (Revista de Historia Social y de las Mentalidades, 2021)
Ernesto Guevara was the main agent of revolutionary ideology after 1959, with the publication of his works and the assumption of foquismo as a doctrine and practice in the left-wing movements of the second half of the 20th century. As of his death in Bolivia in 1967, the failure of this model was verified, however it was adapted to unifying wills around the world. Thus, Che’s physical disappearance is taken as a starting point to analyse the use of his words and his image in the Tricontinental journal, where he occupied a prominent place from the first publication of the special supplement with his text ‘Create two, three ... many Vietnam’ in April 1967.